AVALIAÇÃO DAS AÇÕES DE VIGILÂNCIA EPIDEMIOLÓGICA E CONTROLE DA ESQUISTOSSOMOSE MANSÔNICA NA REGIÃO METROPOLITANA DO ESPÍRITO SANTO - Ribeiro, Mariana Batista (2022)
Schistosomiasis is a parasitic disease, caused by Schistosoma mansoni, that is highly prevalent in rural areas. Espírito Santo is a state of medium endemicity due to the frequent occurrence of cases. This study aims to evaluate the actions of epidemiologi